The Role of the Environmental Service in Community Economic Empowerment through the Waste Bank Program in Mandailing Natal District (Case Study of the Mandailing Natal District Environmental Service) - Suci Fadhilah R. Lubis; Maryam Batubara; Muhammad Arif (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to reveal the role of Mutiara Garbage Bank in Community Economic Empowerment. This research was conducted in Binjai Village, Medan Denai District. The method used in this research is a qualitative research method with a descriptive approach. The instruments used in this research are interviews (interviews) conducted by the author, observation and documentation. This research is field research located at the Waste Bank in Mandailing Natal Regency using purposive sampling method. Data collection techniques using observation methods, interview methods and documentation methods. Using data analysis techniques qualitative descriptive method and using data validity test with triangulation. The results showed that the role of the Waste Bank in Mandailing Natal Regency in an effort to improve the welfare of the community was to conduct economic empowerment activities. Economic empowerment activities carried out by the Waste Bank in Mandailing Natal Regency include waste savings, inorganic waste crafts, and many more. With the Garbage Bank in Mandailing Natal Regency, it can empower the community's economy by involving the potential of the community in handling the waste they have through proper and proper waste sorting and management. With the Garbage Bank in Mandailing Natal Regency, it has an economic impact on the community and makes a clean environment free from waste and improves the quality of public health from air, soil and water pollution caused by garbage.